A case of exploding mangoes - Hanif, Mohammed (New York : Alfred A. Knopf, 2008)
"A novel that reimagines the conspiracies and coincidences leading to the mysterious 1988 plane crash that killed Pakistan's dictator General Zia ul-Haq." "At the center is Ali Shigri: Pakistan Air Force pilot and Silent Drill Commander of Fury Squadron. His father, one of Zia's colonels, committed suicide under suspicious circumstances. Ali is determined to understand what or who pushed his father to such desperation - and to avenge his death." "What he quickly discovers is a snarl of events: Americans in Pakistan, Soviets in Afghanistan, dollars in every hand. But Ali remains patient, determined, a touch world-weary ("You want freedom and they give you chicken korma"), and unsurprised at finding Zia at every turn. He mounts an elaborate plot for revenge with an ever-changing crew: his silk-underwear-and-cologne-wearing roommate; a hash-smoking American lieutenant with questionable motives; the chief of Pakistan's secret police, who mistakenly believes he's in cahoots with the CIA; a blind woman imprisoned for fornication; Uncle Starchy, the squadron's laundryman; and, not least of all, a mango-besotted crow. General Zia - devout Muslim and leering admirer of non-Muslim cleavage - begins every day by asking his chief of security: "Who's trying to kill me?" The answer lies in a conspiracy trying its damnedest to happen..." "Intrigue and subterfuge combine with misstep and luck in this darkly comic book about love, betrayal, tyranny, family - and a world that unexpectedly resembles our own."--BOOK JACKET.
"This is a Borzoi Book."
Keywords: Zia-ul-Haq, Mohammad -- Fiction; Pakistan. -- Air Force -- Fiction; Conspiracies -- Pakistan -- Fiction; Presidents -- Pakistan -- Fiction. -- General books; Political fiction